Combining Ability for Seed Vigour and Viability Traits in Sorghum (Sorghum bicolor (L) Moench) - Ν. ΚΑΝΝΑΒABU; C. ARUNA; S. AUDILAKSHMI; S.S. RAO; N. SEETHARAMA (Seed Research, 2026)
Combining ability analysis was carried out to obtain the information regarding selection of best combiners (parents) for genetic improvement of seed vigour, viability and field emergence potential in sorghum (Sorghum bicolor (L) Moench). The general combining ability estimates revealed that among lines, 463 A had positive and significant gea effects for all the seed parameters of both unaged and aged seeds indicating its capability to combine all the vigour and viability traits. Sorghum restorer line NR 99117 showed the highest positive and significant gea values for all seed parameters excepting shoot length of unaged seeds and root length of aged seeds revealing its wide capability of combining seed vigour and viability. As seed viability alone concerned, tester NR 99105 showed highly positive and significant gea values. It also proved as better general combiner for initial vigour and field emergence of fresh seeds. The line x tester analysis brought out the sorghum line MS 463 A and testers NR 99117 and NR 99105 as better general combiners for seed vigour, viability and field emergence potential traits. The crosses 63 A x NR 99015 and 463 A x NR 99014 proved as best cross combinations among others for seed germination, vigour, viability and field emergence potential by recording positive and significant sca values for all important seed traits.